1996
DOI: 10.1002/1529-0131(199610)9:5<349::aid-anr1790090503>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Reducing work disability associated with rheumatoid arthritis: Identification of additional risk factors and persons likely to benefit from intervention

Abstract: Objective. To study additional risk factors for rheumatoid arthritis @A)-related work disability and to identify the groups of individuals at high risk and thepotentially modifiable factors which place them at risk. Methods. A cross-sectional mail survey was conducted among 469 adults with RA. Work disability was defined as unemployment due to RA. A broad range of explanatory factors was examined, including sociodemographic, health, work, support given by others, and commuting difficulty. Employed and workdisa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
84
5
2

Year Published

1999
1999
2011
2011

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(99 citation statements)
references
References 16 publications
8
84
5
2
Order By: Relevance
“…For example, we also found that work autonomy, functional status, pain, and social support were linked to outcomes (3)(4)(5)(6)(7)(8)11,13). However, unlike other studies, we did not find that depressive symptoms were associated with work outcomes (12), possibly because the prevalence of depressive symptoms in our samples was low.…”
Section: Discussioncontrasting
confidence: 78%
“…For example, we also found that work autonomy, functional status, pain, and social support were linked to outcomes (3)(4)(5)(6)(7)(8)11,13). However, unlike other studies, we did not find that depressive symptoms were associated with work outcomes (12), possibly because the prevalence of depressive symptoms in our samples was low.…”
Section: Discussioncontrasting
confidence: 78%
“…A job with fewer physical requirements and a higher degree of worker autonomy allows a person with arthritis to remain gainfully employed. In addition to limitations in paid work, RA may lead to limitations to satisfy one's personal needs as well as pursuits at home (17).…”
Section: Introductioncontrasting
confidence: 82%
“…[1,3,11,28] Some authors suggested very low work disability rates of up to 13-22% in their group of RA patients. [1,[29][30][31] The differences in work disability rates between our study group and previous studies seem consistent with the results of a recent study of patients with AS in which considerable differences in work status were observed among different European countries. [12,28] The influence of physical function, clinical status measures and socioeconomic conditions on employment in rheumatic diseases may differ according to differences in sociocultural characteristics of each country.…”
Section: Discussionsupporting
confidence: 89%